Antenatal care of pregnant women during pandemic: a phenomenology study - Sudaryanti, Lestari; Mardhika, Amellia; Qona’ah, rina; Mei Tyas, nestasia Pangestu; Chan, Chong Mei (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the experience of pregnant women related to antenatal care during the coronavirus disease-2019 pandemic. Method: The qualitative interpretive phenomenology study was conducted from July to September 2022 in Lamongan General Hospital after approval from Faculty of Nursing, Universitas Airlangga, Surabaya, Indonesia. The sample comprised pregnant women at very high risk in the third trimester during the coronavirus disease-2019 pandemic. Data was collected from the medical records, and subsequently through semi-structured interviews. Data was analysed using the Braun and Clarke thematic analysis. Results: Of the 19 subjects with a mean age of 33.3±4,91 years, 11 (58%) had studied up to high school level and 16(84%) were housewives. There were 5 themes that had a total of 14 sub-themes. The themes were fear of getting pregnant during a pandemic, afraid of losing her baby, losing the support system, adherence to health protocols, and differences in healthcare systems. Conclusion: Pregnancy during the pandemic had an impact on the physical and mental health of women and turned into a terrifying experience. Health workers need to pay attention to the physical and psychological conditions of pregnant women, including antenatal care services that must be provided at least six times directly or by using telemedicine. Keywords: Pregnancy, Prenatal care, Mental health, Anxiety, Telemedicine, Fear, COVID-19.